What motivates rural teachers to retain? A study on Chinese rural teachers' turnover from grounded theory and FsQCA - Cheng, Chao; Diao, Yanjie; Ding, Xing (Frontiers in Psychology, 2023)
In rural areas of China, there is a significant problem with teachers leaving their positions. However, previous studies lack in-depth discussions of the complicated causal relationships between rural teachers’ retention intention and influencing factors. Therefore, this study adopts Grounded theory to construct a theoretical model concerning the factors that influence the retention intention of rural teachers. Based on 408 cases in China, the FsQCA methodology is then employed to develop four configurations divided into two driving paths, including individual single-factor as the core condition; social and individual dual-factor as the core condition. The study has found that (A) when professional identity regards as the core condition, welfare allowance, emotional support, and working environment can be substituted equivalently for each other to increase teachers’ retention intention; (B)career development is neglected for two reasons: first, rural teachers improve themselves to compensate for inadequate social support; second, rural teachers adapt themselves to accept professional stagnation. (C) When the external environment is favorable but rural teachers lack professional identity, they may have a strong intention to retain but lack enthusiasm for teaching. The conclusion can help to clarify the complicated causal relationships among multiple factors that influence rural teachers’ retention intention and contribute to the practical development of the rural teacher workforce.